Ancestralidade e demografia genética de uma amostra da população humana do Rio Grande do Sul - (:unkn) unknown (Universidade Federal do Pampa, 2013)
Mitochondrial markers (mtDNA) and Y chromosome have been used to assess degree of miscigenation. In case of Latin America, main three stocks generated current population: Europeans, Amerindians and Africans. In Rio Grande do Sul as well as Portuguese and Spanish, was significant immigration from other European, especially Germans and Italians. This study aims to evaluate the European, Amerindian and African contribution to formation of gaucho population. For this we used the two uniparental systems and surnames of individuals. Has been analysed 190 volunteers, borned in the seven mesoregions has compound Rio Grande do Sul, those colected a blood sample. It was observed that a high frequency of European contribution (87% on the Y chromosome and 76% in mtDNA), consistent with the couple’s coming of Portuguese immigrants, Germans and Italians. Surnames’ data demonstrate also these surnames are most commonly found in gaucho population.
Ancestrality and genetic demography of a sample of the human population of Rio Grande do Sul
Keywords: Cromossomo Y; Marcadores mitocondriais; DNA; Miscigenação; Chromosome Y; Mitochondrial markers; Miscegenation; CNPQ::CIENCIAS BIOLOGICAS